Leydig Cell Tumor Associated with Testicular Adrenal Rest Tumors in a Patient with Congenital Adrenal Hyperplasia due to 11β-Hydroxylase Deficiency - Nadia Charfi; Mahdi Kamoun; Mouna Feki Mnif; Neila Mseddi; Fatma Mnif; Nozha Kallel; Basma Ben Naceur; Nabila Rekik; Hela Fourati; Emna Daoud; Zainab Mnif; Mourad Hadj Sliman; et al. (Case Reports in Urology)
Congenital adrenal hyperplasia (CAH) describes a group of inherited autosomal recessive disorders characterized by enzyme defects in the steroidogenic pathways that lead to the biosynthesis of cortisol, aldosterone, and androgens. Chronic excessive adrenocorticotropic hormone (ACTH) stimulation may result in hyperplasia of ACTH-sensitive tissues in adrenal glands and other sites such as the testes, causing testicular masses known as testicular adrenal rest tumors (TARTs). Leydig cell tumors (LCTs) are make up a very small number of all testicular tumors and can be difficult to distinguish from TARTs. This distinction is interesting because LCTs and TARTs require different therapeutic approaches. Hereby, we present an unusual case of a 19-year-old patient with CAH due to 11β-hydroxylase deficiency, who presented with TARTs and an epididymal Leydig cell tumor.